Portico : cooking and feasting in Rome's Jewish kitchen - Koenig, Leah (W.W. Norton & Company, Inc., 2023)
"A captivating tour through Rome's centuries-old Jewish community with more than 100 simple, deeply flavorful, vegetable-forward recipes. "Naming the book Portico is my way of saying, 'Welcome. I'm glad you are here.'" A leading authority on Jewish food, Leah Koenig celebrates la cucina Ebraica Romana within the pages of her new cookbook. Portico: Cooking and Feasting in Rome's Jewish Kitchen features over 100 deeply flavorful recipes and beautiful photographs of Rome's Jewish community, the oldest in Europe. The city's Jewish residents have endured many hardships, including 300 years of persecution inside the Roman Jewish Ghetto. Out of this strife grew resilience, a deeply knit community, and a uniquely beguiling cuisine. Today, the community thrives on Via del Portico d'Ottavia (the main road in Rome's Ghetto neighborhood)-and beyond. Leah Koenig's recipes showcase the cuisine's elegantly understated vegetables, saucy braised meats and stews, rustic pastas, resplendent olive oil-fried foods, and never-too-sweet desserts. Home cooks can explore classics of the Roman Jewish repertoire with Stracotto di Manzo (a wine-braised beef stew), Pizza Ebraica (fruit-and-nut-studded bar cookies), and, of course, Carciofi alla Giudia, the quintessential Jewish-style fried artichokes. A standout chapter on fritters-showcasing the unique gift Roman Jews have for delicate frying-includes sweet honey-soaked matzo fritters, fried salt cod, and savory potato pastries (burik) introduced by the thousands of Libyan Jews who immigrated to Rome in the 1960s and '70s. Every recipe is masterfully tailored to the home cook, while maintaining the flavor and integrity of tradition. Suggested menus for holiday planning round out the usability and flexibility of these dishes. A cookbook for anyone who wants to dive more deeply into Jewish foodways, or gain new insight into Rome, Portico features the makers and creators who are keeping Roman Jewish food alive today, transporting us to the bustling streets of the Eternal City while also making us feel-as we cook and eat-very much at home"--